The Expert System for Determining Manual Brew Coffee Techniques and Coffee Beans Using the Forward Chaining Method - Fajarlestari, Maria Karmelia; Dwi Yulianto, Bagas (Department of Information Technology, Universitas Timor, Indonesia, 2024)
An expert system for determining coffee types and brewing techniques was developed using the forward chaining method. All related data, including coffee types, brewing techniques, and coffee flavors and characteristics, were collected. From this data, rules were created for the decision-making process. The decisions made in these rules are derived from expert knowledge. The expert in this research is a barista who works as a coffee maker. The decision-making process is expressed in the form of IF(condition)-ELSE(action). The condition represents the initial facts, consisting of data used in the decision-making process, namely coffee flavors and characteristics. The action represents the conclusion, which is the result: the brewing technique to be used based on the coffee's characteristics and the recommended coffee types based on the coffee flavors. Therefore, this expert system will recommend brewing techniques and coffee types according to the desired coffee flavors and characteristics.